KARAKTERISTIK PASIEN KANKER PADA PEREMPUAN DI POLI ONKOLOGI RSUD HAJI PROVINSI JAWA TIMUR - Aim Matun Nadhiroh; Supatmi Supatmi; Een Hendarsih; Sumariyah Sumariyah; Ari Kusnani; Sri Rahayu; Dita Agustina Mardianti; Rusti Dewi Murni (JOMIS (Journal of Midwifery Science), 2025)
Cancer is one of the leading causes of morbidity and mortality in women worldwide, including in Indonesia. Several types of cancer such as breast cancer, cervical cancer, ovarian cancer, and endometrial cancer have a high prevalence in women. These cancers often have specific risk factors, incidence patterns, and management challenges based on female gender. The purpose of this study was to determine the characteristics of cancer patients in women, especially gynecological oncology and clinical oncology cancer. This type of research is quantitative descriptive, data collection techniques through questionnaires and interviews using primary data. The population in this study were gynecological oncology and clinical oncology cancer patients who visited the Haji Hospital, Surabaya, East Java Province from July to August 2024. The number of samples in this study was 94 patients. The sampling technique in this study was the total population. The results of this study showed that the most cancers in women at the Haji Hospital, East Java Province were breast cancer, which was 52 people, cervical cancer was 15 people. The stage of the disease, almost 40% of patients were at stage 3 and the majority were aged 50-60 years. Age is one of the most significant risk factors for breast and cervical cancer. The incidence increases with age, with a peak in the 50-60 age group. At a young age, genetic and hormonal factors also play an important role. Understanding the relationship between age and breast cancer can help in the development of better screening, prevention and treatment strategies to reduce the burden of cancer in women..